Class Social Situation and Cultural Value Prediction Factors of the Academic Entitlement of College Students. (March 2017) - Hong, Fu-Yuan; Huang, Der-Hsiang; Lin, Min-Pei; Lin, Hung-Yu
This study measured the level of academic entitlement in college students using a performance promotion goal questionnaire, an academic entitlement group norm questionnaire, a cultural value orientation questionnaire, and an academic entitlement questionnaire, with 297 college students. The research findings of this study could be used to identify teachers' behavior and class situation factors that could significantly predict the academic entitlement of college students. The academic entitlement group norm could be regarded as a normative mechanism affecting the relationship between individualism and academic entitlement, as well as between performance promotion goals and academic entitlement. Finally, the research results were discussed, and relevant suggestions were proposed for schools, teachers, and future research.